(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the speech apparatus and its anatomical and physiological properties scientifically and theoretically. The study highlights the structure of the speech apparatus, its central and peripheral parts, and its importance in the process of speech formation. Also, the harmonious functioning of the respiratory, vocal and articulation organs is considered as the main factor in the correct formation of speech.